Some Games Used to Teach Vocabulary to Young Learners - Azwar Arifin (TEFLIN Journal: A publication on the teaching and learning of English, 2003)
Many English classes in Indonesia are now filled with many young learners. For example, a class may consist of 25 - 30 students. As a result, this may not be effective. The students could feel bored, stuck, and noisy, furthermore, if the class is filled by many young learners the atmosphere cannot be supportive anymore. To overcome the problem, the English teacher can vary his/her teaching techniques, one of which is playing games. They can undoubtedly, entertain the students Wierus and Wierus (1994:218) said that in easy, relaxed atmosphere which is created by using games, students remember things faster and better. This paper discusses the benefit of using games, the approriacy of using games, and some current games to teach vocabulary.